Extract of acai-berry inhibits osteoclast differentiation and activity. (August 2016) - Brito, C.; Stavroullakis, A.T.; Ferreira, A.C.; Li, K.; Oliveira, T.; Nogueira-Filho, G.; Prakki, A.
Highlights: Acai berry extract is not cytotoxic to RAW 264.7 cell line stimulated by RANKL. Acai berry extract inhibited osteoclastogenesis in a dose dependent manner. Acai berry extract inhibits osteoclasts activity. Acai berry extract regulates osteoclasts cytokine secretion. Abstract: Osteoclastogenesis is the major cellular event responsible for bone loss and is triggered by inflammation. Acai-berry has proven anti-inflammatory effects. However, there is a lack of evidence for its effects on osteoclastogenesis. Thus, the aim of this study was to determine whether acai-berry extract (ABE) could inhibit osteoclastogenesis and osteoclast activity in vitro . The secretion of cytokines by osteoclasts has been also evaluated. RAW 264.7 cells were stimulated with RANKL (50 ng/mL) and treated with various concentrations of ABE (25–100 μg/mL) to verify: cell viability (MTT), total protein concentration (BCA), osteoclast differentiation and activity, and cytokine secretion. Cell viability and protein assays showed no toxicity to RAW cells for the tested ABE concentrations (p > 0.05). ABE also showed a dose-dependent inhibition of osteoclastogenesis and osteoclast activity evaluated by tartrate-resistant acid phosphatase (TRAP) and hydroxylapatite resorption assay, respectively (p < 0.05). ABE decreased the secretion of interleukin (IL)-1α, -6 and tumor necrosis factor alpha while increasing the secretion of IL-3, -4, -13 and interferon gamma when compared to the control group (p < 0.05). Results of this study showed that acai-berry extract inhibits osteoclast differentiation and activity possibly due to the modulation of a vast number of cytokines produced by osteoclast precursor cells.